A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

Naturalness as a basis for incorporating marine biodiversity into life cycle assessment of seafood - Anna K. Farmery; Sarah Jennings; Caleb Gardner; Reg A. Watson; Bridget S. Green (The International Journal of Life Cycle Assessment, 2017)

Assessing the inclusion of seafood in the sustainable diet literature - Anna K Farmery; Caleb Gardner; Sarah Jennings; Bridget S Green; Reg A Watson (Fish and Fisheries, 2017)
The literature on sustainable diets is broad in its scope, and application yet is consistently supportive of a move away from animal‐based diets towards more plant‐based diets. The positioning of seafood within the sustainable diet literature is less clear. A literature review was conducted to examine how the environmental impacts of seafood consumption are assessed and what conclusions are being drawn about the inclusion of seafood in a sustainable diet. Seafood is an essential part of the global food system but is not adequately addressed in most of the sustainable diet literature. Aquaculture, the world's fastest growing food sector, was considered by very few papers. Seafood consumption was commonly presented as a dilemma due to the perceived trade‐offs between positive health outcomes from eating seafood and concerns of overfishing. A number of studies included seafood as part of their sustainable diet scenario, or as part of a diet that had lower impacts than current consumption. Most of the indicators used were biophysical, with a strong focus on greenhouse gas emissions, and very few studies addressed biological or ecological impacts. The assessment of seafood was limited in many studies due to relevant data sets not being incorporated into the models used. Where they were used, data sources and methodological choices were often not stated thereby limiting the transparency of many studies. Both farmed and wild‐capture production methods need to be integrated into research on the impacts of diets and future food scenarios to better understand and promote the benefits of sustainable diets.